New Triterpenoids from the Leaves of Heritiera littoralis and Their Anti-Inflammatory Activity - Chenyang Ren; Xiaoqin Liang; Rui Pi; Jiwen Xin; Bo Yang; Qingfang Zheng; Yanqin Li; Jun Li; Yanjun Zhang (Molecules)
Six new triterpenoids, heritieras C–H (1–6), along with thirteen known triterpenoids (7–19), were isolated from the leaves of Heritiera littoralis. Their structures were identified by spectroscopic analysis, including 1D and 2D nuclear magnetic resonance (NMR), high-resolution electrospray ionization mass spectrometry (HRESIMS), and by comparison with the literature. Anti-inflammatory activity of the isolates was evaluated using the lipopolysaccharide (LPS) stimulated RAW 264.7 cell model. Among the isolated triterpenoid, compounds 1, 12, 16, 17, and 18 demonstrated inhibitory activity against nitric oxide (NO) release, in which compound 18 exhibited the best activity with an IC50 value of 18.13 μM. The potential anti-inflammatory mechanism was investigated using molecular docking. The triterpenoids from H. littoralis could be served as potential candidates for the development of new anti-inflammatory agents.